ANCA Testing in Clinical Practice: From Implementation to Quality Control and Harmonization - Damoiseaux, Jan (Frontiers in Immunology, 2021)
Analyses for the presence of anti-neutrophil cytoplasmic antibodies (ANCA) are important in the diagnostic work-up of patients with small vessel vasculitis. Since current immuno-assays are predominantly designed for diagnosis of patients with ANCA-associated vasculitis (AAV), implementation in routine clinical practice, internal and external quality control, and harmonisation are focussed on this particular use. However, ANCA testing may also be relevant for monitoring therapy efficacy and for predicting a clinical relapse in AAV patients, and even for diagnostic purposes in other clinical situations. In the current review, the topics of implementation, quality control, and standardisation versus harmonisation are discussed while taking into account the different applications of the ANCA assays in the context of AAV.